Regarding confirming remaining 3468.302t steel structure elements list - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the confirmation about remaining 3468.302t steel structure elements list for BRACU new campus project.